REVITALISASI INVESTASI PENGEMBANGAN ENERGI PANAS BUMI DI INDONESIA - Ragimun, Ragimun (Badan kebijakan Fiskal, 2013)
Premises as a country that is being build, requiring electrical energy very much. It is therefore necessary for the utilization of various sources of insufficiency. During this energy from fossil sources dominate the national energy needs. But this fossil energy sources will eventually run out. So that the necessary renewable energy, among other things of geothermal energy. This energy is in addition to friendly neighborhood also has a reserve that very much. Recorded 26 percent of world geothermal energy in Indonesia. However, until recently the development of new geothermal energy range from 4 percent The main obstacle is the issue of investment is still limited, as well as policy and institutional reforms to increase investment. It is therefore necessary to revitalize geothermal energy investments through several fiscal and non fiscal incentives in the form of investment attraction such as the selling price of electricity energy geothermal interest. Current selling price of geothermal electrical energy for U.S. 0.97. This needs to be re-evaluated, in order to attract investors in geothermal development in Indonesia.